IMPROVING YOUNG LEARNERS’ ENGLISH VOCABULARY AND CONFIDENCE THROUGH FUN LEARNING AT BAN BANGOISINAE SCHOOL - Maulidina, Amma; Yidayeh, Umee (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2026)
This community service program was conducted at Ban Bangoisinae School, Yala, Thailand, to address primary students limited English vocabulary mastery and low confidence in basic oral communication. Preliminary observations indicated that many fourth-grade students were reluctant to use English and experienced difficulties in constructing simple sentences. To address these challenges, a fun learning approach was implemented through interactive classroom instruction, complemented by a supplementary program entitled One Word One Sentence Weekly Vocabulary. The program emphasized student centered and enjoyable learning activities, including games, flashcards, repetition, and guided sentence construction. The activities were implemented over a two-month period comprising 26 instructional sessions. The findings demonstrate notable improvements in student engagement, vocabulary retention, and confidence. Approximately 70% of students in class 4/1 and 75% of students in class 4/2 actively participated in learning activities and successfully completed assigned tasks. Moreover, more than 80% of students were able to recall and appropriately use newly introduced vocabulary. These results suggest that the fun learning approach is effective in enhancing motivation, basic English competence, and learner confidence within an international community service context.